Case Report: Severe rash/desquamation induced by sorafenib in an uHCC patient and its clinical management - Yan Lin; Ping-Yu Liu (Frontiers Media S.A., 2022)
Background: Sorafenib-related dermatological toxicity is a well-known adverse reaction that can severely affect therapeutic outcomes. Rash/desquamation with its variable manifestations is one of the common clinical presentations. Currently, no standard continuum of care for sorafenib-related rash/desquamation has been established.Case summary: A 75-year-old woman with colorectal cancer who developed unresectable hepatocellular carcinoma (uHCC) received, six years later, sorafenib 400 mg twice daily. She developed a Grade-3 Common Terminology Criteria for Adverse Events (CTCEA) rash and bullae bilaterally on her lower extremities after 2 weeks of sorafenib use. Rash and blisters began to appear on the left calf and then merged as large bullae full of liquid and spread to both lower extremities. The bullae then erupted and skin began to slough off, which affected the patient's normal daily functioning. To lessen the condition, sorafenib was stopped permanently and dexamethasone intravenous (IV) infusion at 5 mg daily for 3 days and piperacillin/tazobactam were used. The skin dried without exudate or ulcerations after a month.Conclusion: For severe (CTCAE Grade 3 or above) sorafenib-related rash/desquamation, short-term corticosteroid pulse therapy at large doses is usually effective with routine skin care, and antibiotics can be considered if infection is present. Permanent cessation of sorafenib should be considered if severe manifestations such as erythema multiforme (EM) and Steven-Johnson syndrome (SJS) are suspected.